Assessing the patient safety competencies of healthcare professionals: a systematic review - Okuyama, Ayako (BMJ Group, 2011)
BACKGROUND: Patient safety training of healthcare professionals is a new area of education. Assessment of the pertinent competencies should be a part of this education. This review aims to identify the available assessment tools for different patient safety domains and evaluate them according to Miller's four competency levels. METHODS: The authors searched PubMed, MEDLINE, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, psycINFO and the Education Resource Information Center (ERIC) from the start of each database to December 2010 for English-language articles that evaluated or described tools for the assessment of the safety competencies of individual medical and/or nursing professionals. Reports on the assessment of technical, clinical, medication and disclosure skills were excluded. RESULTS: Thirty-four assessment tools in 48 studies were identified: 20 tools for medical professionals, nine tools for nursing professionals, and five tools for both medical and nursing professionals. Twenty of these tools assessed the two highest Miller levels (‘shows how’ and ‘does’) and four tools were directed at multiple levels. Most of the tools that aimed at the higher levels assessed the skills of working in teams (17 tools), risk management (15 tools), and communication (11 tools). Internal structure (reliability, 22 tools) and content validity (14 tools) when described were found to be moderate. Only a small number of tools addressed the relationship between the tool itself and (1) other assessments (concurrent, predictive validity, eight tools), and (2) educational outcomes (seven tools). CONCLUSIONS: There are many tools designed to assess the safety competencies of healthcare professionals. However, a reliable and valid toolbox for summative testing that covers all patient safety domains at Miller's four competency levels cannot yet be constructed. Many tools, however, are useful for formative feedback.